Sequential V(A)/Q distributions in the normal rabbit by micropore membrane inlet mass spectrometry - Baumgardner, J E; Choi, I C; Vonk-Noordegraaf, A; Frasch, H F; Neufeld, G R; Marshall, B E (Journal of applied physiology (1985), 2000)
We developed micropore membrane inlet mass spectrometer (MMIMS) probes to rapidly measure inert-gas partial pressures in small blood samples. The mass spectrometer output was linearly related to inert-gas partial pressure (r(2) of 0.996-1.000) and was nearly independent of large variations in inert-gas solubility in liquid samples. We infused six inert gases into five pentobarbital-anesthetized New Zealand rabbits and used the MMIMS system to measure inert-gas partial pressures in systemic and pulmonary arterial blood and in mixed expired gas samples. The retention and excretion data were transformed into distributions of ventilation-to-perfusion ratios (V(A)/Q) with the use of linear regression techniques. Distributions of V(A)/Q were unimodal and broad, consistent with prior reports in the normal rabbit. Total blood sample volume for each VA/Q distribution was 4 ml, and analysis time was 8 min. MMIMS provides a convenient method to perform the multiple inert-gas elimination technique rapidly and with small blood sample volumes.